Desarrollo de un sistema para administrar medicamentos a adultos mayores a través del reconocimiento de código de barras y su implementación en el robot Nao - Navas Reascos, Gabriel Ernesto (2017)
The project deals with the intercommunication between the Robot of the Salesian Polytechnic University and an older adult; in order to administer medicines through barcode recognition. Because over time human beings face social, psychic and biological factors that affect their mental health causing them to not take their medications at the prescribed time and even confuse them being necessary the presence of another person to assist them. For this reason, was proposed a project with the NAO robot to help reducing mistakes in the consumption of medication in older adults and, the consequences of those mistakes. The document details what is and how a bar code reader works, such as how to make the performing communication between the reader and the robot NAO, using an Arduino and its USB HOST SHIELD complement; Additionally, it is detailed how to create a database inside the robot NAO which contains the bar code of the medicine, the time to be administered and the name of the patient. In addition, It is pointed out the method used in the project for the mobilization and navigation of the NAO robot in a created environment, the algorithms used for the recognition of the patient's face, the measurements and weight of the recommended medications for an optimal operation and the tests carried out as well As the results obtained.